Historical review of the special education system in R. Macedonia and Turkey - Ramo Akgün, Nergis; Petrov, Risto; Karovska Ristovska, Aleksandra; Ajdinski, Goran (Faculty of Philosophy, Skopje, 2016)
Organized social care for people with special educational needs in R. Macedonia, expressed through care, education and rehabilitation, begins after World War II. Before that, on the territory of present Republic of Macedonia there wasn't organized education and rehabilitation for children with special educational needs. In Republic of Turkey, the Ottoman period attributed great importance to the treatment of people with disabilities. In this paper, we analysed historical data of special primary education systems for five categories of disabilities; intellectual disability, visual impairment, hearing impairment, physical disabilities and autism in Macedonia and Turkey. The aim of our research was to make a historical overview of the special education system for all categories of disability in both countries. Therefore, the main research question is: In which of the two countries special schools are having longer tradition? In order to answer this question, we made five sub-questions linked with the category of disability and the state. The results showed that Republic of Turkey has a longer tradition of educating children with special educational needs for three categories of disabilities: visual impairments, hearing impairments and autism, while for the children with intellectual and physical disabilities, the treatment in Macedonia is organized earlier. This qualitative research has theoretical, comparative and descriptive character. We used the method of descriptive and comparative analysis. As a technique in qualitative research, we chose analysis of documentation of data received from relevant institutions. All data was analysed according to the research questions, setting the appropriate conclusions and suggestions.
Keywords: historical review, special education system, Republic of Macedonia, Republic of Turkey